Two Sources of again-ambiguities: Evidence from Degree-Achievement Predicates - Pedersen, Walter (Proceedings of the Amsterdam Colloquium, 2009)
This paper provides evidence that again-ambiguities derive from two distinct sources, with the precise nature of a particular ambiguity being dependent on the particular type of predicate (Result-State or Degree Achievement) present in the sentence. Previous research has focused primarily on sentences containing Result-State predicates (e.g. to open) rather than Degree Achievements (e.g. to widen), and has located the source of the ambiguity in the scope that again takes with respect to BECOME in a syntactically decomposed predicate. I argue that entailment facts preclude such an analysis from applying to sentences containing Degree Achievements and again. Instead, I propose that Degree Achievement predicates should be decomposed into comparative structures, and that the ambiguity in such sentences arises from the scope again takes with respect to a comparative Degree Phrase, rather than a BECOME operator.